The Role of Local Wisdom in Disaster Mitigation: A Systematic Literature Review (SLR) Approach - Syuryansyah, Syuryansyah; Habibi, Fikri (International Journal of Disaster Management, 2023)
This research analyzes the role and implementation of local wisdom in disaster management in Indonesia. The study focuses on the three stages of disaster management: pre-disaster, during the disaster, and post-disaster. The approach of "Disaster Management based on Local Wisdom" serves as the foundation, integrating cultural values, traditional knowledge, and communal practices with scientific methods. This study utilizes various literature sources and field data to illustrate how local communities apply local wisdom in facing potential disasters. The research findings highlight significant contributions from local values such as mutual assistance, understanding natural signs, and community involvement in disaster-aware communities. The synergistic collaboration between scientific knowledge and local wisdom proves to be an effective approach in disaster management. The research findings underscore the importance of integrating local values in a holistic disaster management strategy to enhance preparedness and mitigate risks within communities